Assessment of retinoblastoma RNA reflux after intravitreal injection of melphalan. Issue 3 (31st October 2017) - Winter, Ursula; Nicolas, Michael; Sgroi, Mariana; Sampor, Claudia; Torbidoni, Ana; Fandiño, Adriana; Chantada, Guillermo L; Munier, Francis L; Schaiquevich, Paula
Abstract : Background: Intravitreal injection of chemotherapy in retinoblastoma eyes with vitreous seeds may lead to a risk of extraocular tumour dissemination that has not been assessed so far. Aims: To develop a sensitive and clinically feasible technique to assess for potential retinoblastoma cell reflux after intravitreal injection of melphalan. Methods: Filter papers were cut in 6 mm diameter circles and sterilised before use. Eyes with retinoblastoma vitreous seeds (group D, International Classification) received weekly intravitreal melphalan injections (20 µg or 30 µg/dose) followed by cryotherapy as part of local treatment. Immediately after finishing the injection and cryotherapy, filter papers were placed on the injection site and on the cryoprobe tip to assess for the expression of the cone-rod homeobox gene (CRX) by real-time qPCR as a surrogate of retinoblastoma RNA. The assay was developed and validated to determine sensitivity, linearity, recovery, repeatability and reproducibility. Results: The assay for quantitation of CRX expression was linear in the range of 1 to 1000 cells. The lowest limit of detection was one retinoblastoma cell and allowed to recover 100% of the cell load in external supplementation. A total of 14 eyes received 22 cycles of intravitreal melphalan and were evaluated for potential extraocular tumour cell dissemination using the developed technique. None of the cycles were positive for CRX in samples from the scar or from the cryoprobe tip. Conclusions: A sensitive and simple method of tumour cell assessment has been developed that can be used in the clinics to assess for potential extraocular dissemination after intravitreal injections to assure its performance.